A Book On A Proposed House Museum For An Unknown Crying Man. - Khaled, Mahmoud; El Adl, Sara (Berlin : Berliner Künstlerprogramm des DAAD)
El Adl, Sara ; El Baroni, Bassam ; Nasr, Edwin ; Elsisi, Hannah ; Awad, Hicham ; Fayed, Ismail ; Attalah, Lina
boek
Keywords: Khaled, Mahmoud